The end of work theological critiques of capitalism - Hughes, John (Blackwell, 2007)
Hughes surveys 20th century theologies of work, contrasting differing approaches to consider the 'problem of labour' from a theological perspective. It is aimed at theologians concerned with how Christianity might engage in social criticism, as well as those interested in the connection between Marxist and Christian traditions.
Auch angezeigt u.d.T.: Theology and work
Includes bibliographical references and index
Keywords: Marx, Karl -- 1818-1883; Christentum; Kapitalismus; Religion; Capitalism -- Religious aspects -- Christianity; Work -- Religious aspects -- Christianity; Labor -- Religious aspects -- Christianity; Utility theory; Theologie; Kritik